Job Satisfaction and the Good Soldier: The Relationship Between Affect and Employee "Citizenship". - Bateman, T. S.; Organ, D. W. (Academy of Management Journal, 1983)
A measure of a wide array of employee activities on the job was completed by employees' supervisors at two points in time; employees reported their own job satisfaction via the Job Descriptive Index. Implications of relationships much higher than typically found in the job satisfaction–performance literature are discussed.